Pendekatan Muhasabah: Solusi Atasi Degradasi Moral Siswa Madrasah melalui Penilaian Sikap Sosial - Raikhan, Raikhan (Edudeena : Journal of Islamic Religious Education, 2024)
Abstract: Moral degradation among madrasah students is a serious concern in the current era. Researchers are interested in studying the implementation of the muhasabah approach in overcoming the moral degradation of madrasah students. This research uses a descriptive qualitative approach with multisites and uses observation, interview and documentation data collection techniques. Data sources include teachers and students at three madrasas, namely MA Tarbiyatut Tholabah Lamongan, MA Matholi'ul Anwar Lamongan, and MA Salafiyah Lamongan. The data analysis process uses case analysis of field data, including checking, organizing, and coding as well as cross-case analysis. The research results show that consistent application of the muhasabah approach can increase students' self-awareness of moral values, improve social behavior, and reduce actions that conflict with religious and social norms. There are four principles used by the three madrasas, namely contextual, communicative, open and fair principles. This is supported by an attitude assessment, including discipline, responsibility, honesty, self-confidence and enthusiasm. The implication of this research is the importance of integrating the muhasabah approach in the educational curriculum in madrasas to shape better student character through assessing social attitudes.